2019
DOI: 10.1051/0004-6361/201935409
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and kinematic structure of extremely high-velocity molecular jets in the Serpens Main star-forming region

Abstract: Context. Outflows are one of the first signposts of ongoing star formation. The fastest molecular component to the protostellar outflows -extremely high-velocity (EHV) molecular jets -are still puzzling since they are seen only rarely. As they originate deep inside the embedded protostar-disk system, they provide vital information about the outflow-launching process in the earliest stages. Aims. The first aim is to analyze the interaction between the EHV jet and the slow outflow by comparing their outflow forc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 92 publications
(153 reference statements)
4
54
0
Order By: Relevance
“…Lower-velocity (∼10-20 km s −1 ) wide-angle outflows are also seen in the CO emission around the high-velocity jets (Hull et al 2014(Hull et al , 2017. Studies of the chemistry of the outflows have identified SiO in the high-velocity jet and wideangle outflows, while HCN and H 2 CO are only seen in the slower wings, consistent with a lower C/O ratio in the jet (Tychoniec et al 2019). Mid-infrared Spitzer observations also find jets in H 2 and various atomic emission lines (e.g., [Fe II]); however, interpreting which source is driving each outflow is complicated by the complexity of the outflows and the lower Spitzer resolution (Dionatos et al 2014).…”
Section: B14 Serpens Main Smm 1: Linear Groupmentioning
confidence: 73%
“…Lower-velocity (∼10-20 km s −1 ) wide-angle outflows are also seen in the CO emission around the high-velocity jets (Hull et al 2014(Hull et al , 2017. Studies of the chemistry of the outflows have identified SiO in the high-velocity jet and wideangle outflows, while HCN and H 2 CO are only seen in the slower wings, consistent with a lower C/O ratio in the jet (Tychoniec et al 2019). Mid-infrared Spitzer observations also find jets in H 2 and various atomic emission lines (e.g., [Fe II]); however, interpreting which source is driving each outflow is complicated by the complexity of the outflows and the lower Spitzer resolution (Dionatos et al 2014).…”
Section: B14 Serpens Main Smm 1: Linear Groupmentioning
confidence: 73%
“…If the red-and blueshifted lobes have different position angles, we average them together. Hull et al (2017b), Aso et al (2019), Tychoniec et al (2019) and Le Gouellec et al (2019) for Serpens Emb 6, Emb 8 and Emb 8(N). Tobin et al (2019) for BHR71 IRS1 and IRS2.…”
Section: Discussionmentioning
confidence: 99%
“…The emission of MP4 is elongated to the north-east toward mm core 6. All species having an enhanced emission toward MP4 and MP5 are known to trace shocked regions caused by protostellar outflows (Leurini et al 2011;Benedettini et al 2013;Moscadelli et al 2013;Shimajiri et al 2015;Palau et al 2017;Tychoniec et al 2019;Okoda et al 2020;Taquet et al 2020). There is enhanced c-C 3 H 2 emission toward the north and south of core 2 (Fig.…”
Section: Line Integrated Intensitymentioning
confidence: 99%